The lung microbiota in early rheumatoid arthritis and autoimmunity. Issue 1 (December 2016) - Scher, Jose; Joshua, Vijay; Artacho, Alejandro; Abdollahi-Roodsaz, Shahla; Öckinger, Johan; Kullberg, Susanna; Sköld, Magnus; Eklund, Anders; Grunewald, Johan; Clemente, Jose; Ubeda, Carles; Segal, Leopoldo; et al.
Abstract Background Airway abnormalities and lung tissue citrullination are found in both rheumatoid arthritis (RA) patients and individuals at-risk for disease development. This suggests the possibility that the lung could be a site of autoimmunity generation in RA, perhaps in response to microbiota changes. We therefore sought to test whether the RA lung microbiome contains distinct taxonomic features associated with local and/or systemic autoimmunity. Methods 16S rRNA gene high-throughput sequencing was utilized to compare the bacterial community composition of bronchoalveolar lavage fluid (BAL) in patients with early, disease-modifying anti-rheumatic drugs (DMARD)-naïve RA, patients with lung sarcoidosis, and healthy control subjects. Samples were further assessed for the presence and levels of anti-citrullinated peptide antibodies (including fine specificities) in both BAL and serum. Results The BAL microbiota of RA patients was significantly less diverse and abundant when compared to healthy controls, but similar to sarcoidosis patients. This distal airway dysbiosis was attributed to the reduced presence of several genus (i.e., Actynomyces andBurkhordelia ) as well as reported periodontopathic taxa, includingTreponema, Prevotella, andPorphyromonas . While multiple clades correlated with local and systemic levels of autoantibodies, the genusPseudonocardia and various related OTUs were the only taxa overrepresented in RA BAL and correlated with higher disease activity and erosions. Conclusions Distal airway dysbiosis is present in untreated early RA and similar to that detected in sarcoidosis lung inflammation. This community perturbation, which correlates with local and systemic autoimmune/inflammatory changes, may potentially drive initiation of RA in a proportion of cases.